The Influence of Workload and Work Environment on Employee Job Satisfaction at the Dinas Perhubungan Province Jawa Timur - Kustini, Kustini; Ramadhani, Rizky (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to investigate how Workload and Work Environment influence job satisfaction among employees at the East Java Provincial Transportation Office. This research adopts a quantitative approach, assessing variables through a Likert scale. The sample size was determined using Slovin's formula, resulting in a sample of 65 employees from a total population of 180. Data analysis was conducted using Partial Least Squares (PLS) analysis. The results reveal that Workload significantly affects employee job satisfaction, and similarly, Work Environment also exerts a significant impact on job satisfaction.